2005
DOI: 10.1108/13552510510616478
|View full text |Cite
|
Sign up to set email alerts
|

Fuzzy set‐valued and grey filtering statistical inferences on a system operating data

Abstract: PurposeIntends to address a fundamental problem in maintenance engineering: how should the shutdown of a production system be scheduled? In this regard, intends to investigate a way to predict the next system failure time based on the system historical performances.Design/methodology/approachGM(1,1) model from the grey system theory and the fuzzy set statistics methodologies are used.FindingsIt was found out that the system next unexpected failure time can be predicted by grey system theory model as well as fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 5 publications
0
8
0
Order By: Relevance
“…Thus, an adjustment coefficient method based on set-valued statistics is used to adjust the weight. And setvalued statistics have been used in many articles [48][49][50][51].…”
Section: Methods For Adjusting the Weight Of First-level Indexesmentioning
confidence: 99%
“…Thus, an adjustment coefficient method based on set-valued statistics is used to adjust the weight. And setvalued statistics have been used in many articles [48][49][50][51].…”
Section: Methods For Adjusting the Weight Of First-level Indexesmentioning
confidence: 99%
“…The grey system theory have also been successfully employed in many prediction applications with the use of grey model GM (1, 1), such as geosciences, engineering, agriculture, medicine, meteorology, natural sciences, and bioscience [17][18][19][20][21][22][23][24][25][26].…”
Section: Preliminariesmentioning
confidence: 99%
“…Up to now, the conventional method for vehicle prediction can be roughly divided into four types: time series method, regression method, expert-based method and neural network-based method. Guo and Love (2005) indicated that these methods need not only a large amount of historical data but also typical distributions, and use the statistical method to analyse the characteristics of the system. Thus, these methods are limited by the historical data used.…”
Section: Introductionmentioning
confidence: 99%